PLTHV ANALISIS POTENSI PEMBANGKIT LISTRIK TENAGA HIDRO VORTEX (PLTHV) DI DESA SAWAH KEMBANG: ANALISIS POTENSI PEMBANGKIT LISTRIK TENAGA HIDRO VORTEX (PLTHV) - Ilmi Rizki Imaduddin; Dwi Agus Fahreza; Lukmanul Hakim; Faris Rahman Maulana (POLITALA PRESS, 2022)
Abstract. Electricity is one of the most basic elements of life on earth. Sawah Bunga Hamlet is located in a mountainous area to the south of Probolinggo Regency, which is one of the mountainous hamlets that has not yet received electricity supply from PLN. In this study, a survey was conducted of 16 hydro vortex power plants located in Sawah Kembang Hamlet which will be investigated. Furthermore, the data collection process is rpm, voltage, current, frequency, and electric power by using a formula to produce a theoretical value for each generator. From this research, it was found that 13 power plants were still running and 3 plants were damaged, where the large potential generated by the hydro vortex power plant produced an average frequency of 65.89 Hz with an average of 157.714 watts of electrical power generated at each. each generator. The results of this study indicate that Dusun Sawah Bunga can apply renewable energy to get to an Energy Independent Village as a pilot village.